"Extinction of Indic (Quechua) language" in Chachapoyas, 1792 - Solís Fonseca, Gustavo (2003)
We publish in this issue of Lengua y Sociedad, a document from the 18th century, 1792. It is a report that the parish priest of Santo Thomas de Quilla (now Santo Tomás, in the Department of Amazonas), named Francisco Gutiérrez de Cos, sent to Don Juan Manuel Hernández, who held the position of Subdelegate of Chachapoyas. The document in reference is a letter of October 20, 1792 that Gutiérrez de Cos sends in "reply" to the Oficio sent to him by Juan M. Hernández the previous month.